Antibodies against glycoprotein 2 display diagnostic advantages over ASCA in distinguishing CD from intestinal tuberculosis and intestinal Behçet's disease. Issue 2 (February 2018) - Zhang, Shulan; Luo, Jing; Wu, Ziyan; Roggenbuck, Dirk; Schierack, Peter; Reinhold, Dirk; Li, Ji; Zeng, Xiaofeng; Zhang, Fengchun; Qian, Jiaming; Li, Yongzhe
Abstract : OBJECTIVES: : There is an increasing need to identify reliable biomarkers for distinguishing Crohn's disease (CD) from other gastrointestinal disorders sharing similar clinical and pathological features. This study aimed at evaluating the diagnostic potential of antibodies to zymogen granule glycoprotein GP2 (aGP2) in a large, well‐defined Chinese cohort with a special focus on their role in discriminating CD from intestinal Behçet's disease (BD) and intestinal tubercolosis (ITB). METHODS: : A total of 577 subjects were prospectively enrolled, including 171 patients with CD, 208 patients with ulcerative colitis (UC), 71 with BD, 57 with ITB and 70 healthy controls (HC). aGP2 and anti‐Saccharomyces cerevisiae antibodies (ASCA) were determined by ELISA. Perinuclear antineutrophil cytoplasmic antibodies were tested by indirect immunofluorescent assay. RESULTS: : aGP2 IgG and IgA levels were significantly elevated in patients with CD compared with those in patients with UC, intestinal BD, and ITB and HC. Conversely, ASCA IgG levels were not different between CD and intestinal BD patients, whereas ASCA IgA levels did not discriminate CD from intestinal BD and ITB patients. aGP2 IgA and IgG displayed a better assay performance (larger areas under the curve) over ASCA IgA and IgG in differentiating CD from disease controls ( P <0.05). ASCA IgA did not discriminate CD from disease controls. aGP2 IgA and/or IgG was significantly associated with penetrating disease (B3) and ileal CD (L1) ( P <0.05), whereas ASCA IgA and/or IgG was not. CONCLUSIONS: : In comparison with ASCA, aGP2 distinguishes CD from intestinal BD or ITB as disease controls more efficiently, aiding in the differential diagnosis of IBD.